The paradox of the internationalization of constitutional law in Africa : Reflections on normative, instituional and political interactions in the ECOWAS area - (:unkn) unknown (My University, 2017)
It is difficult to deny that something has happened to constitutional lawunder the combined effect of the internationalization of law and the construction of thecommunity. Indeed, constitutional law is internationalized, regionalized in an exponentialmovement. Africa in general and the ECOWAS area in particular do not escape the globaldynamics of modern constitutionalism. Thus, it has been observed that theinternationalization of constitutional law on the African continent, which takes the form of aprocess of impact, influence or sometimes constraints, leads both to a horizontalreconfiguration of constitutional and a vertical redistribution of power within the state. Onthe other hand, at the supranational level, this dynamic and intense process, which marks anopening up of legal systems and promotes communication between legal orders, is reflectedin a phenomenon of integration and progressive harmonization of the state's constitutionalsystems around democratic standards The ECOWAS Protocol on Democracy and GoodGovernance of 2001. The dialectic is, in the end, paradoxical in that the internationalizationof constitutional law in Africa and more particularly in the ECOWAS area proves to be aphenomenon Disrupting the constitutional legal systems of the state and the community,and at the same time an instrument of material (fundamental) and structural (democraticpolitical rule, rule of law) convergence of these orders through standards which constitutethe common constitutional heritage.
Keywords: African Research